توجهات السياسة النقدية في جذب الاستثمارات الاجنبية المباشرة في العراق للمدة 2004-2017 (Al Kut Journal of Economics and Administrative Sciences, 2021)
تعد السياسة النقدية من أهم مجالات السياسات الاقتصادية الكلية التي تواجه تحديات التي خلفها الانفتاح الاقتصادي في العراق بعد عام 2003 من خلال جذب اكبر قدراً ممكناً من الاستثمار الاجنبي المباشر إلى العراق .ويهدف البحث إلى تحديد اهم مؤشرات السياسة النقدية ودورها في تحفيز وجذب الاستثمارات الاجنبية المباشرة في العراق للمدة 2004-2017 ، وأهتم بتشخيص مؤشرات السياسة النقدية وآلية انتقالها على بيئة الاستثمار الاجنبي المباشر ، وتناول البحث عرض وتحليل مؤشرات السياسة النقدية وربطها مع حركية الاستثمار الاجنبي المباشر في العراق خلال مدة الدراسة . واستنتجت الدراسة أن السياسة النقدية عملت بعد عام 2003 على فرز قانون البنك المركزي العراقي رقم 56 لسنة 2004 والذي منح الاستقلالية للبنك المركزي العراقي لبناء ركائز قوية للاستقرار الاقتصادي وتهيئة المناخ المناسب لجذب وتحفيز الاستثمار الاجنبي المباشر.وان اهم توصيات الدراسة اكدت على ضرورة تنويع الاقتصاد العراقي وعدم الاعتماد على القطاع النفطي والنهوض بالقطاعات الاقتصادية الآخرى ( القطاع الزراعي والقطاع الصناعي )، والقضاء على الفساد المالي والاداري والعمل على تحسين البنى التحتيه وتطويرها من أجل تحفيز وجذب الاستثمار الاجنبي المباشر في العراق .AbstractMonetary policy is one of the most important areas of macroeconomic policies that face challenges left by the economic openness in Iraq after 2003 by attracting the largest possible amount of foreign direct investment to Iraq.  The research aims to identify the most important indicators of monetary policy and its role in stimulating and attracting foreign direct investment in Iraq for the period 2004-2017, and I am interested in diagnosing monetary policy indicators and its transmission mechanism on the foreign direct investment environment (foreign direct investment mobility), and the research dealt with presenting and analyzing monetary policy indicators and linking them with Mobility of foreign direct investment in Iraq during the study period. The study concluded that monetary policy worked after 2003 on sorting out the Central Bank of Iraq Law No. 56 of 2004, which granted independence to the Central Bank of Iraq to build strong pillars of economic stability and create the appropriate climate to attract and stimulate foreign direct investment.And the most important recommendations of the study emphasized the necessity of diversifying the Iraqi economy and not relying on the oil sector and the advancement of other economic sectors (the agricultural sector and the industrial sector), eliminating financial and administrative corruption and working to improve and develop the infrastructure in order to stimulate and attract foreign direct investment in Iraq.